Face Emotion Recognition - A survey - Kartigayan, M.; Mohamed Rizon, Mohamed Juhari; Sazali, Yaacob; Nagarajan, R. (Oita University, 2009)
Organized by Oita University (Japan), 23rd - 25th January 2006 at Oita, Japan.